Coupled Coincidence Points for Mixed Monotone Random Operators in Partially Ordered Metric Spaces - Jiang, Binghua; Shi, Lu; Xu, Shaoyuan (Abstract and Applied Analysis, 2014)
The aim of this work is to prove some coupled random coincidence theorems for a pair of compatible mixed monotone random operators satisfying weak contractive conditions. These results are some random versions and extensions of results of Karapınar et al. (2012). Our results generalize the results of Shatanawi and Mustafa (2012).